2015
DOI: 10.1002/mabi.201500273
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of Hydrogels Regulates Cellular Reprogramming Efficiency Through Mesenchymal‐to‐Epithelial Transition and Stemness Markers

Abstract: The stiffness of hydrogels has been reported to direct cell fate. Here, we found that the stiffness of hydrogels promotes the reprogramming of mouse embryonic fibroblasts into induced pluripotent stem cells (iPSCs). We prepared cell culture substrates of various stiffnesses (0.1, 1, 4, 10, and 20 kPa) using a polyacrylamide hydrogel. We found that culture on a soft hydrogel plays an important role in inducing cellular reprogramming into iPSCs via activation of mesenchymal-to-epithelial transition and enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 53 publications
1
39
1
Order By: Relevance
“…Knock-down of these kinases that disrupt the F-actin network, including TESK1 and LIMK2 that phosphorylate the actin-binding protein cofilin [102], induce dramatic cellular phenotypic changes, turns fibroblasts into epithelial cells, and enhances iPSC efficiency. Similarly, MEFs cultured on a soft hydrogels increased MET and iPSC formation [103]. Together these data suggest a key role for cellular mechanics and tension maintained by cytoskeleton in regulating MET during iPSC formation.…”
Section: Met Required For Stem Cell Reprogramingmentioning
confidence: 94%
“…Knock-down of these kinases that disrupt the F-actin network, including TESK1 and LIMK2 that phosphorylate the actin-binding protein cofilin [102], induce dramatic cellular phenotypic changes, turns fibroblasts into epithelial cells, and enhances iPSC efficiency. Similarly, MEFs cultured on a soft hydrogels increased MET and iPSC formation [103]. Together these data suggest a key role for cellular mechanics and tension maintained by cytoskeleton in regulating MET during iPSC formation.…”
Section: Met Required For Stem Cell Reprogramingmentioning
confidence: 94%
“…Topographical cues may affect the direct reprogramming of fibroblasts into induced neurons [18]. The stiffness of hydrogels could regulate the cellular reprogramming efficiency [19]. However, the influence of flat culture substrates on cellular reprogramming has received little attention so far.…”
Section: Introductionmentioning
confidence: 99%
“…0.1 kPa polyacrylamide gels induced MET and increased expression of Oct4 and Sox2 on adhered cells during reprogramming relative to the 20 kPa gels [27]. Similarly in an earlier study, softening of substrate stiffness has been shown to achieve reprogramming in HEK-293 cells simply through changes in actin force without any transcription factors [28].…”
Section: Biomaterials In Ipsc Reprogrammingmentioning
confidence: 86%